2006
DOI: 10.1103/physrevlett.97.207205
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Current and Field Driven Depinning of Domain Walls on Their Structure and Chirality in Permalloy Nanowires

Abstract: A magnetic domain wall (DW) injected and pinned at a notch in a permalloy nanowire is shown to exhibit four well-defined magnetic states, vortex and transverse, each with two chiralities. These states, imaged using magnetic force microscopy, are readily detected from their different resistance values arising from the anisotropic magnetoresistance effect. Whereas distinct depinning fields and critical depinning currents in the presence of magnetic fields are found, the critical depinning currents are surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
358
2
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 362 publications
(384 citation statements)
references
References 23 publications
17
358
2
7
Order By: Relevance
“…5. The same behavior was found in experiments [11]. This chirality dependence of the depinning field can also be well explained by our theory.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…5. The same behavior was found in experiments [11]. This chirality dependence of the depinning field can also be well explained by our theory.…”
Section: Resultssupporting
confidence: 74%
“…Therefore the anticlockwise wall whose width is larger near the notch should correspond to smaller depinning fields, as can be seen from Eq. (11).…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism of CIDWM was first investigated. The microscopic structure of a DW was observed by using advanced imaging techniques, [21][22][23] from which it was found that there are four types of DWs: transverse and vortex DWs with clockwise and counterclockwise spin rotation. It was revealed that among the DW types, the vortex DW is more mobile than the transverse one.…”
Section: Progress In Study Of Current-induced Domain Wall Motionmentioning
confidence: 99%
“…A complex DW structure limited the comparison between experiment and theory. 21) Transformations between a transverse DW and vortex DW, and vice versa, made it difficult to control the DW position by a current pulse. 22) A relatively large DW (∼a few hundreds nm) was thought to limit the density of devices.…”
Section: Progress In Study Of Current-induced Domain Wall Motionmentioning
confidence: 99%
See 1 more Smart Citation